Prompt contributions to the dilepton yield in heavy ion collisions - Hüfner, Jörg; Ivanov, Yuri P.; Raufeisen, Jörg (Arxiv, 2000)
The mass spectrum is calculated for those dileptons which are produced in the early phase of a heavy ion collisions via the direct production NN -> (l^+)(l^-)X and via the Compton process GN -> (l^+)(l^-)X with prompt gluons radiated in preceding NN interactions. Both mechanisms produce a mass spectrum which decreases steeply with invariant mass of the l^+l^- pair and which is below the CERES data for Pb-Au collisions by about one order of magnitude.